Political uncertainty and corporate debt financing: empirical evidence from China. Issue 13 (16th March 2019) - Lv, Miaochen; Bai, Manying
ABSTRACT: We examine the influence of political uncertainty on corporate debt financing under the Chinese highly specialized political system. A new reasonable and effective alternative indicator, official turnover reason, is constructed to measure different political uncertainty level. Robust results suggest that listed companies will keep low debt financing level and smooth debt financing volatility under political uncertainty, which will be weakened during the global financial crisis. We also find that the listed company will raise equity financing level while overall financing is significantly reduced. In addition, SOEs are more sensitive to political uncertainty than non-SOEs, as they have stronger political connections with government officials.